Estimation of Ground Water Level (GWL) for Tropical Peatland Forest Using Machine Learning - Li L.; Sali A.; Liew J.T.; Saleh N.L.; Ahmad S.M.S.; Ali A.M.; Nuruddin A.A.; Aziz N.A.; Sitanggang I.S.; Syaufina L.; Nurhayati A.D.; Nishino H.; et al. (Institute of Electrical and Electronics Engineers Inc., 2023)
Artificial intelligence; Fires; Forestry; Groundwater; Internet of things; Mean square error; Sensor nodes; Tropics; Water levels; Fire weather index; Forest reserves; Ground water level; IoT system; Machine-learning; Malaysia; Neural-networks; Peat land; Trans-boundary; Weather index systems; Drought